Constructing Robust Solid Electrolyte Interface via ZrO2 Coating Layer for Hard Carbon Anode in Sodium-Ion Batteries - Yuteng Gong; Chengxin Yu; Yu Li; Ji Qian; Chuan Wu; Ying Bai (Batteries, 2022)
Hard carbon (HC) has attracted extensive attention due to its rich material source, environmental non-toxicity, superior sodium storage capacity, and lower sodium storage potential, and is considered most likely to be a commercial anode material for sodium-ion batteries (SIBs). Nevertheless, the limited initial Coulombic efficiency (ICE) of HC is the main bottleneck hindering its practical application. To alleviate this issue, herein, a ZrO2 coating was skillfully constructed by using a facile liquid phase coating method. The ZrO2 coating can act as a physical barrier to prevent direct contact between the HC surface and the electrolyte, thus effectively reducing irreversible sodium adsorption and inhibiting the continuous decomposition of the electrolyte. Meanwhile, this fresh interface can contribute to the generation of a thinner solid electrolyte interface (SEI) with high ionic conductivity. As a result, the ICE of the ZrO2-coated HC electrode can be optimized up to 79.2% (64.4% for pristine HC). Furthermore, the ZrO2-coated HC electrode delivers outstanding cyclic stability so that the capacity retention rate can reach 82.6% after 2000 cycles at 1 A g−1 (55.8% for pristine HC). This work provides a flexible and versatile surface modification method to improve the electrochemical property of HC, and hopefully accelerate the practical application of HC anodes for SIBs.